Two new species of Panaietis (Copepoda: Cyclopoida: Anthessiidae) associated with vetigastropods (Gastropoda) in coastal waters of southern Japan - Uyeno, Daisuke (Zootaxa, 2019)
Two new species of the genus Panaietis (Copepoda: Cyclopoida: Anthessiidae) inhabiting the inside of the mouth cavities of marine snails are described from shallow waters of southern Japan. Panaietis bobocephala sp. nov. collected from the small abalone, Haliotis asinina (Vetigastropoda: Lepetellida: Haliotidae), is mainly characterized by the well-developed posterolateral corners of tergite on first pediger, the pointed spines on legs 1 to 5, the maxilla with two teeth, and the leg armature formula. Panaietis flavellata sp. nov. from Angaria neglecta (Vetigastropoda: Trochida: Angariidae) is characterized by the combination of following: leg 5 is situated on ventral side of the fifth pediger, inner margin of the second segment of antenna greatly protruded, and the leg armature formula.